Mutant mouse models implicate a role for mGluR1/5, prolyl isomerase (Pin1) and Homer1a interactions in wakefulness - Keenan, Brendan T.; Strus, Ewa; Lin, Raozhou; Chan, May; Lian, Jie; Galante, Raymond; Worley, Paul; Pack, Allan I.; Naidoo, Nirinjini (Frontiers in Neuroscience, 2025)
IntroductionHealthy sleep and wake are integral to good health and occur when an organism is able to maintain long bouts of both sleep and wakefulness. Homer proteins have been shown to be important for sleep in both Drosophila and mice. For example, genetic deletion of Homer1a in mice results in failure to sustain long bouts of wakefulness. Homer1a has also been shown to amplify mGluR activity by facilitating binding of the prolyl isomerase Pin1 to mGluR. This study uses mouse models to evaluate whether the Homer1a null sleep phenotype may be dependent on the mGluR-Pin1 interaction and examines sleep/wake behavior.MethodsEEG recordings were used to determine and compare sleep and wake in three different mouse models and their littermate control mice. Mouse models included: mGluR(TS-AA) knock-in mice in which Pin1 binding is prevented and activity-dependent prolyl isomerization of mGluR is inhibited; mGluR(F-R) knock-in mice in which Homer binding is eliminated but Pin1 binding is allowed; and a Homer1a null, mGluR(F-R) double mutant mouse to evaluate whether Pin1 binding can rescue the Homer1a knock-out phenotype. Sleep-wake behavior was analyzed using traditional summary measures and a spike-and-slab mixture distribution to better characterize microarchitecture.ResultsKnock-in mGluR(TS-AA) mice display a reduced ability to sustain long bouts of wakefulness during the active lights off period, recapitulating part of the previously observed wake phenotype of the Homer1a knock-out mouse. Alteration of the Homer binding site to mGluR in mGluR(F-R) knock-in mice has no effect on the sleep phenotype, whereas crossing the mGluR(F-R) knock-in into the Homer null background resulted in increased duration of long wake bouts, suggesting a restored ability to maintain wakefulness, with other sleep/wake characteristics similar to littermate mice.ConclusionThese studies highlight the role of Pin1 binding to mGluR as a potential mechanism in the control of sleep/wake behavior. Future studies should explore whether other binding partners of Homer and mGluR also affect sleep and wake.